Experimental Mathematics. Volume 14, Number 1, 2005 - A K Peters (A K Peters, 2009)
No access to content A Diophantine Property Associated with Prime Twins Full TextPDF (171.6 KB) Author P. Shiu 1-6 No access to content Heuristics for the Whitehead Minimization Problem Full TextPDF (152.8 KB) Authors R. M. Haralick, A. D. Miasnikov and A. G. Myasnikov 7-14 No access to content Classification of Solvable Lie Algebras Full TextPDF (175.0 KB) Author W. A. de Graaf 15-25 No access to content Special Values of the Standard Zeta Functions for Elliptic Modular Forms Full TextPDF (291.9 KB) Author Hidenori Katsurada 27-45 No access to content On Lower Bounds of the Density of Delone Sets and Holes in Sequences of Sphere Packings Full TextPDF (239.0 KB) Authors G. Muraz and J. -L. Verger-Gaugry 47-57 No access to content Einstein Metrics on Exotic Spheres in Dimensions 7, 11, and 15 Full TextPDF (138.2 KB) Authors Charles P. Boyer, Krzysztof Galicki, János Kollár and Evan Thomas 59-64 No access to content A New Algorithm for the Computation of Logarithmic l-Class Groups of Number Fields Full TextPDF (206.9 KB) Authors Francisco Diaz Y Diaz, Jean-François Jaulent, Sebastian Pauli, Michael Pohst and Florence Soriano-Gafiuk 65-74 No access to content Forcing Relations for Homoclinic Orbits of the Smale Horseshoe Map Full TextPDF (206.6 KB) Author Pieter Collins 75-86 No access to content The Asymptotic Distribution of Exponential Sums, II Full TextPDF (358.8 KB) Author S. J. Patterson 87-98 No access to content A Software Package for the Numerical Integration of ODEs by Means of High-Order Taylor Methods Full TextPDF (1.2 MB) Authors Àngel Jorba and Maorong ZouNo access to content Wildly Ramified Galois Representations and a Generalization of a Conjecture of Serre Full TextPDF (168.2 KB) Author Darrin Doud